Characterisation of Artocarpus heterophyllus Fibre Reinforced Composite - Chua, Tian Hao; Nicholas Kuan, Hoo Tien (UNIMAS Publisher, 2018)
Natural fibre reinforced polymer composite (NFRPC) has successfully replaced other synthetic fibre for applications in automobile, sport equipment, furniture, electrical appliances, etc. Artocarpus heterophyllus or jackfruit are mass produced in most South East Asia, but most of the parts other than the fruit would go to waste. In this study, Artocarpus heterophyllus fibre reinforced high density polyethylene (HDPE) composite was fabricated and tested for its mechanical properties, such as tensile and hardness properties. Artocarpus heterophyllus fibres were made into sheets using traditional paper making process, before being laminated with HDPE films using hot press method. Different volume fraction of fibre laminates were produced: 10%, 13%, 17% and 21%. The study shows that composite with 10%, 13% and 17% fibre volume fraction exhibits better tensile strength and hardness value than neat HDPE, while composites with 13%, 17% and 21% fibre volume fraction exhibit higher tensile modulus than neat HDPE. The optimum fibre content for the Artocarpus heterophyllus composite is 17%.